Training and Mentoring to Strengthen Literacy and Numeracy in the Learning Recovery of the Ogan Ilir Region - Syarifuddin, Syarifuddin; Aksan, Hamdi; Santri, Didi Jaya; Izzah, Izzah; Fathurohman, Apit; Oktapiani, Rani; Lestari, Dea (Pascasarjana Universitas Mataram, 2024)
The literacy and numeracy training and mentoring program in Ogan Ilir aims to enhance the competencies of junior high school teachers in supporting the improvement of literacy and numeracy in learning recovery. This program consists of outreach activities, training, and intensive mentoring over two days designed to help teachers improve literacy and numeracy in their respective schools. As an initial step, a pretest was given to the participants to measure their initial understanding of literacy and numeracy. During the training, participants were provided with materials through interactive sessions, group discussions, and hands-on practice to design a literacy and numeracy improvement program. At the end of the training, a post-test was conducted to evaluate the improvement in participants' understanding and skills, with results showing an increase in most participants. This program concludes with monitoring and evaluation through reports and visits to schools to ensure the implementation of training results in their respective educational environments. Overall, this activity can strengthen teachers' literacy and numeracy skills in supporting learning recovery